A Microfluidic Device for Simple and Rapid Evaluation of Multidrug Efflux Pump Inhibitors - Iino, Ryota; Nishino, Kunihiko; Noji, Hiroyuki; Yamaguchi, Akihito; Matsumoto, Yoshimi (Frontiers in Microbiology, 2012)
Recently, multidrug-resistant pathogens have disseminated widely owing essentially to their increased multidrug efflux pump activity. Presently, there is a scarcity of new antibacterial agents, and hence, inhibitors of multidrug efflux pumps belonging to the resistance–nodulation–cell division (RND) family appear useful in the treatment of infections by multidrug-resistant pathogens. Moreover, recent progress in microfabrication technologies has expanded the application of nano/micro-devices to the field of human healthcare, such as the detection of infections and diagnosis of diseases. We developed a microfluidic channel device for a simple and rapid evaluation of bacterial drug efflux activity. By combining the microfluidic device with a fluorogenic compound, fluorescein-di-β-D-galactopyranoside, which is hydrolyzed to a fluorescent dye in the cytoplasm of Escherichia coli, we successfully evaluated the effects of inhibitors on the RND-type multidrug efflux pumps MexAB–OprM and MexXY–OprM from Pseudomonas aeruginosa in E. coli. Our new method successfully detected the MexB-specific inhibitory effect of D13-9001 and revealed an unexpected membrane-permeabilizing effect of Phe-Arg-β-naphthylamide, which has long been used as an efflux pump inhibitor.